Oral delivery of protein antigens to Atlantic salmon - Klaric, G (UCL (University College London), 2015)
During recent years, the use of functional ingredients in aquaculture industry has increased dramatically. Accordingly, there are a broad range of functional feeds available for use in fish farming. As a result, there is ongoing research which focuses on developing oral delivery systems for fish. Variety of products can be incorporated into alginate matrices to avoid damage from the low pH and proteolytic enzymes encountered in the digestive tract of fish. However, there has been very little research reported on the effectiveness of those oral delivery systems with respect to performance within fish feed and fish. Furthermore, the reported particle sizes used within alginate delivery systems require further reduction to be suitable for effective association within feed pellets. Additionally, it is essential that active compounds are released at the right place in fish. In this study, encapsulation technology capable of providing an economical and high throughput method for producing fine alginate beads (≤10 µm) was assessed. Post-coating examination with the micro-tomography (micro-CT) equipment confirmed the presence of alginate particles inside the pellet in large numbers. According to our observations in an enzyme assay, the active compounds are released at the most favourable site in Atlantic salmon which is the distal intestine. There is also evidence to suggest that alginateencapsulated protein antigens when released in the intestine are capable of crossing the intestinal epithelial layer. Similarly, in the assessment of intraperitoneal priming/oral boosting strategy against infectious pancreatic necrosis (IPN), alginate-encapsulated IPN antigens boosted immune response in salmon. This could be seen in significant up-regulation of relevant genes measured by quantitative PCR and specific antibody response detected in an ELISA assay. The results of these investigative studies significantly improve understanding of the issues regarding incorporation of delivery systems into fish feed in the current ...